Fractal dielectric resonator antenna for ultra wideband wireless communication systems - Azari, Abolfazl (2015)
Recently, the integration of multiple wireless technologies has enforced the modern communication systems to operate in multiple frequency bands. In addition, the high demand for faster and reliable services in these systems leads to the necessity of a large data transmission capacity and therefore a wide operational bandwidth. Beside this, advanced wireless devices face with some strict features concerning the size and weight. A major component of modern wireless devices is the antenna which should meet the mentioned requirements. Hence, a small physical size and multi band performance are the major design requirements for antennas in wireless communication systems. Fractals are recognized by their self similarity and space filling properties. Applying fractal geometries to antenna design donates a good solution for addressing the proper miniaturization and multi band performances. On the other hand, using dielectric materials in antenna design leads to dielectric resonator antennas (DRAs) which are characterized by compact size, a wide operational bandwidth and a high radiation efficiency. The thesis initially discusses and evaluates recent and past developments taken place in fractal antenna and DRA areas through a review of literature. In the beginning of the design, the popular Koch fractal geometry and its monopole configurations are discussed. Then, a new fractal geometry that looks like Koch is chosen as a candidate geometry, primarily because its similarity dimension is more than the similarity dimension of Koch geometry. In addition, various DRA structures reported in the literature are considered in order to extract the suitable guidelines for design procedure. Extensive numerical simulations are presented to obtain an efficient design. As a result, the conic is chosen as an optimized dielectric resonator shape for superimposing to the proposed fractal monopole antenna. Accordingly, an ultra wideband monopole antenna based on the combination of a new fractal geometry and a new dielectric resonator configuration is presented. The numerical and experimental results confirm that, this novel design is an ultra wideband antenna with a usable bandwidth of 2 – 40 GHz. This huge bandwidth is the major advantage of the proposed antenna amongst conventional ultra wideband antenna types. Radiation patterns are studied at different frequencies, and the gain is found to be reasonable across the entire operating bandwidth. The most popular applications of this antenna are for wireless LAN IEEE 802.11 a/b/g and body area network (BAN). Also, the possible applications in X and Ku bands are broadband satellite communication and military applications.